Intervenção dietoterápica na síndrome metabólica e sua associação com o perfil genético da intolerância à lactose - Araújo, Edilene Maria Queiroz (2016)
Metabolic syndrome (MS) is a complex disorder with a strong genetic basis and multifactorial etiology. Insulin resistance (IR) causes MS and it can be triggered by intestinal inflammation like the use of lactose in patients intolerant of this carbohydrate. It was found that variants in the lactase gene are associated with lactase non persistence LNP and MS in a population sample of Salvador/Bahia; and whether these variants are modifying the response to diet-therapeutic intervention in patients with this syndrome; also compared the biochemical test of lactose tolerance (LTT) with genetic diagnosis; and tested the association of mutations in the lactase gene with cofactors SM (TGL, HDL-C, blood pressure, glucose levels, waist circumference), with anthropometric variables (Arm Circumference, Body Mass Index, Hip Circumference, hip-waist ratio,lean massand fat mass percentages) and other factors associated with MS: insulin, total cholesterol, LDL-C, VLDL-C, C-reactive protein, HOMA-IR, renal function (creatinine, urea, uric acid, microalbuminuria) and vitamin D. There were two studies: a case-control with 257 cases (MS) and 210 controls and other clinical trial study, which was conducted with three types of diet in patients with metabolic syndrome: diet 1 - No lactose; Diet 2 - Lactose and energy restriction; Diet 3 - Only energy restriction. In all groups were also evaluated for nine SNPs in the lactase (LCT) gene. The genotyping of SNPs was carried out by TaqMan assays. Data were analyzed using SPSS, 20.0, and the Hardy-Weinberg Equilibriumhaplotype frequencies were calculated using Arlequin, 2000 program. The results showed that all diets improve several MSaspects after two months of intervention, especially in the diet 1, that also decreased inflammation, insulin resistance and dyslipidemia (LDL-C). In addition,it was the diet that most took out patients of the MS: 2.72 times more likely to get out of MS than diet 3. LNP was high in both cases and controls. There was compatibility between clinical diagnosis for LNP by Lactose Tolerance Test and two of the studied SNPs, they were rs4988253 and rs182549, those that have proved functional studies. Thus, it is suggested the analysis of LCT gene polymorphisms before the nutritional therapeutics for patients with MS, as well as to take out the lactose in their diet.